2011
DOI: 10.1007/s11096-010-9475-9
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a pharmacist-led sequential antimicrobial therapy strategy: a controlled before-and-after study

Abstract: This controlled before and after study demonstrates successful implementation of a pharmacist-led antimicrobial stewardship strategy. Duration of IV antimicrobial treatment reduced significantly and the timeliness of switch significantly improved. This study may be used as a template for the introduction of further pharmacist-led antimicrobial stewardship initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 16 publications
3
69
0
5
Order By: Relevance
“…These guidelines consider antibiotic restriction and pre-authorization as the most effective methods in controlling the use of antimicrobial agents (Dellit et al, 2007). In agreement with the IDSA and SHEA antimicrobial stewardship guidelines, Dunn et al (2011) demonstrated that a pharmacist-driven antimicrobial stewardship programme significantly decreased the number of days of intravenous antimicrobial therapy and the number of days until intravenous antimicrobial therapy was transitioned to oral therapy.…”
Section: Introductionmentioning
confidence: 85%
“…These guidelines consider antibiotic restriction and pre-authorization as the most effective methods in controlling the use of antimicrobial agents (Dellit et al, 2007). In agreement with the IDSA and SHEA antimicrobial stewardship guidelines, Dunn et al (2011) demonstrated that a pharmacist-driven antimicrobial stewardship programme significantly decreased the number of days of intravenous antimicrobial therapy and the number of days until intravenous antimicrobial therapy was transitioned to oral therapy.…”
Section: Introductionmentioning
confidence: 85%
“…Interventions were in following areas antimicrobial management [17][18][19][20][21][22], targeted drug programmes [23][24][25][26], multidimensional clinical pharmacy service [27][28][29], paediatric programmes [30,31], renal specialist [32,33], pharmacotherapeutic optimisation [34,35], intensive care service [36,37] and neurosurgery [38]. All intervention types have been identified in previous reviews of the literature [10][11][12][13].…”
Section: Clinical Pharmacy Interventionsmentioning
confidence: 99%
“…Five of the studies included a comparator, either in the form of a randomised controlled trial [19] or a pre-and post- intervention comparison [17,18,20,22]. One study was a prospective audit [21].…”
Section: Antimicrobial Managementmentioning
confidence: 99%
“…90 OPS assessment and evaluation of a patient's ability to tolerate oral medications and diet can expedite the conversion of IV antibiotics to the oral formulation, especially in patients where high-risk neutropenia is downgraded with fever defervescence, neutrophil recovery, and resolution of mucositis. 91,92 As mentioned earlier, genetic variation in UGT1A1 is associated with irinotecan-induced neutropenia. Pharmacist monitoring of these patients would help avert potential infectious complications.…”
mentioning
confidence: 79%